Analysis of investment and decision-making based on ESG token platform under jump-diffusion. Issue 4 (12th March 2023) - Li, Renzhong; Fei, Chen; Pan, Haifeng; Fei, Weiyin
ABSTRACT: Token financing is operated by a platform based on blockchain technology. This paper mainly studies the influence of ESG factors on the decision-making of various participants on the platform and analyses the influence of the persistent shock environment on the operation of the token platform. We first characterise developers' token holdings by a jump-diffusion stochastic differential equation. Besides, the nonpecuniary benefits specific to the ESG environment is introduced to the developers' objective function and an incentive of government capital gain tax for green platform developers is also considered. Moreover, the Hamilton–Jacob–Bellman (HJB) equation satisfied by the developers' value function is derived while the equilibrium price of the token is obtained. Then, we compare the differences between some features, which include users' transaction volume, speculators' transaction volume and expected token returns, on the green platform (ESG score greater than 0) and the same features on the brown one (ESG score less than 0). We also analyse the impact of speculators' ESG preferences on the expected token returns, users' and speculators' transaction volume. Finally, by using numerical simulation, we illustrate the impact of the intensity of persistent shock and investment risk (token return volatility) on the operation of the token platform.